Calculations of spin-polarized Goos–Hänchen displacement in magnetically confined GaAs/AlxGa1−xAs nanostructure modulated by spin–orbit couplings. (13th March 2018) - Lu, Mao-Wang; Chen, Sai-Yan; Zhang, Gui-Lian; Huang, Xin-Hong
Abstract: We theoretically investigate Goos–Hänchen (GH) displacement by modelling the spin transport in an archetypal device structure—a magnetically confined GaAs/Al x Ga1− x As nanostructure modulated by spin–orbit coupling (SOC). Both Rashba and Dresselhaus SOCs are taken into account. The degree of spin-polarized GH displacement can be tuned by Rashba or Dresselhaus SOC, i.e. interfacial confining electric field or strain engineering. Based on such a semiconductor nanostructure, a controllable spatial spin splitter can be proposed for spintronics applications.